Experimental Studies on Fiber Reinforced Soil Stabilized with Lime and Fly Ash - Sarkar, Raja; Devi, Dipika; Tamang, Santosh Kumar (International Journal of Integrated Engineering, 2024)
This study investigates the enhancement in strength of fiber-reinforced soil stabilized with lime and fly ash, focusing on key parameters essential for highway design and construction i.e., California Bearing Ratio (CBR) and compaction characteristics. Laboratory tests were conducted to determine the CBR values, Maximum Dry Density (MDD), and Optimum Moisture Content (OMC) of soil stabilized with varying percentages of fly ash (FA) and lime, and reinforced with different types and percentages of fibers, specifically coir fibers (CF) and polypropylene fibers (PF). The addition of stabilizing agents (fly ash and lime) to the fiber-reinforced soil was found to increase the OMC and decrease the MDD. Notably, a significant increase in the CBR value was observed up to an optimum content of these admixtures. However, adding fibers beyond a certain percentage resulted in the sample breaking. This study is novel in its comprehensive evaluation of both natural (coir) and synthetic (polypropylene) fibers in combination with traditional stabilizers (fly ash and lime), offering insights into the optimal mix for enhancing soil strength. The findings contribute to more efficient and durable highway construction practices by identifying the balance between fiber reinforcement and chemical stabilization.